Answer:
2(x - 3)(x - 9)
Step-by-step explanation:
Given
f(x) = 2x² - 24x + 54 ← factor out 2 from each term
= 2(x² - 12x + 27) ← factor the quadratic
Consider the factors of the constant term (+ 27) which sum to give the coefficient of the x- term (- 12)
The factors are - 3 and - 9 , since
- 3 × - 9 = + 27 and - 3 - 9 = - 12 , thus
x² - 12x + 27 = (x - 3)(x - 9) and
f(x) = 2(x - 3)(x - 9) ← in factored form
Answer:
-6v - 12
v = -2
Step-by-step explanation:
Simplify:
- Apply the rules of the distributed property by multiplying -2 and 3v and -2 and -6: -6v - 12
Solve:
- Now that we have our simplified form, we can find what v is. First divide each side by -6 to cancel out the -6 next to v. It should now look like this: v = -2
Answer:
144
Step-by-step explanation:
Answer:
-45n-2
Step-by-step explanation:
Let's get rid of parenthesis first using distributive property!
-10n-12+10-35n
Combine like terms!
-10n-35n--12+10
-45n-2 would be the final expression